2023
DOI: 10.3390/plants12101968
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Profiling and Antioxidant Activity of Tanacetum vulgare L. Wild-Growing in Latvia

Abstract: The Tanacetum vulgare L. (Tansy) has several ethnobotanical uses, mostly related to the essential oil and sesquiterpene lactones, whereas information regarding other compounds is scarce. This research is designed to characterize the phenolic compounds (flavonoids, phenolic acids, and tannins) to analyze the thujone (which is toxic in high concentrations) content and to detect the antioxidant activity (DPPH assay) of extracts. The main highlights of our work provide a chemical profile of phenolic compounds of T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 59 publications
1
9
0
Order By: Relevance
“…Asteraceae family plants contain more terpenes (sesquiterpene lactones and santonin [ 13 ]) and phenolics (phenolic acids and lignans [ 30 ]). Tansy from Latvia contains different phenolic compounds; in a study from Latvia, chemical compounds in extracts of tansy were tested, where total flavonoids, phenolic acids, total phenols, tannins, specific phenols (quinic acid, gallic acids, catechin, chlorogenic acid, caffeic acid, rutin, quercetin, kaempferol, and apigenin) and essential oils (thujone) was detected [ 31 ]. Overall, phenolic compounds are the secondary metabolites, which are often related to antiparasitic effect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Asteraceae family plants contain more terpenes (sesquiterpene lactones and santonin [ 13 ]) and phenolics (phenolic acids and lignans [ 30 ]). Tansy from Latvia contains different phenolic compounds; in a study from Latvia, chemical compounds in extracts of tansy were tested, where total flavonoids, phenolic acids, total phenols, tannins, specific phenols (quinic acid, gallic acids, catechin, chlorogenic acid, caffeic acid, rutin, quercetin, kaempferol, and apigenin) and essential oils (thujone) was detected [ 31 ]. Overall, phenolic compounds are the secondary metabolites, which are often related to antiparasitic effect.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, phenolic compounds are the secondary metabolites, which are often related to antiparasitic effect. The leaf extracts (135–219 mg GAE/g) contain more phenolic compounds than flower extracts (127–155 mg GAE/g) [ 31 ]. This could be the reason why in this study leaf extracts showed stronger anthelmintic activity than flower extracts.…”
Section: Discussionmentioning
confidence: 99%
“…Also, luteolin, O-caffeoyl glucoside (C15H18O9), pontica epoxide (C13H10O), 6-methoxykaempferol and 5,7,3'-trihydroxy-3,6,4',5'-tetramethoxyflavone were identified in tansy root extracts in 50% methanol. The majority of the compounds identified in tansy extracts in 50% methanol (Table 3) had previously been characterized [1,[4][5][6][7][8][9][10]. It should be noted that some common flavonoids (apigenin, rutin, (iso)quercitrin, eupatorin, hispidulin, etc.…”
Section: Chemical Composition Of Non-volatile Components In T Vulgare...mentioning
confidence: 99%
“…In the ethno-pharmacology of many European countries (including Lithuania), the plant has been used for many purposes: as an anthelmintic remedy, for the healing of neurological, digestive, skin, support-motion, and respiratory system diseases [1][2][3][4][5][6]. Recent investigations have shown that T. vulgare is a vast natural resource with a wide range of pharmacological properties, including antioxidant [2][3][4][5][7][8][9][10][11], antibiotic [3,10], anti-inflammatory [3,11], cytotoxic [1][2][3]7,11], antimicrobial [1,2,[10][11][12], anthelmintic [13], diuretic [14], vascular [15], antibacterial [8,10,16], enzyme inhibition [7,16] and neuroprotective activity [7,17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation